Parsons family papers - Parsons, Enoch, 1769-1846.; Parsons, Samuel Holden, 1737-1789.; Parsons, Samuel Holden, 1800-1871.
Correspondence, legal documents, account book, newspaper clippings, printed matter, and other papers chiefly of Samuel Holden Parsons (1737-1789), his son, Enoch Parsons, and Enoch's son, Samuel Holden Parsons (1800-1871). Includes a 1778 letter from General Parsons to his friend, American loyalist William Walter, in which he argues the colonists' cause. Also includes material on Parsons's work for the Ohio Company relating to land development near Marietta, Ohio, and in the Western Reserve. Other topics include Indians in the Old Northwest, the nullification controversy, and family matters. Family correspondents include Mary Sullivan Parsons Dickson, Enoch Thomas Parsons, Henry Ethelbert Parsons, Jonathan Parsons, and Mehetabel Mather Parsons. Other correspondents include Richard Butler, Oliver Ellsworth, Jonathan Greenleaf, Benjamin Huntington, Joel Munsell, Israel Putnam, Benjamin F. Wade, and Elisha Whittlesey.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Parsons family of Connecticut and Ohio. Family members represented include Samuel Holden Parsons (1737-1789), Continental Army officer; his son, Enoch Parsons, public official and banker of Middletown and Hartford, Conn.; and Enoch's son, Samuel Holden Parsons (1800-1871), lawyer and banker of Middletown, Conn.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dickson, Mary Sullivan Parsons, -- -1841 -- Correspondence; Butler, Richard, -- 1743-1791 -- Correspondence; Ellsworth, Oliver, -- 1745-1807 -- Correspondence; Greenleaf, Jonathan, -- 1785-1865 -- Correspondence; Huntington, Benjamin, -- 1736-1800 -- Correspondence; Munsell, Joel, -- 1808-1880 -- Correspondence; Parsons, Enoch Thomas, -- -1830 -- Correspondence; Parsons, Henry Ethelbert -- Correspondence; Parsons, Jonathan, -- 1705-1776 -- Correspondence; Parsons, Mehetable Mather, -- 1743-1802 -- Correspondence; Putnam, Israel, -- 1718-1790 -- Correspondence; Wade, B. F. -- 1800-1878 -- Correspondence; Walter, William, -- 1737-1800 -- Correspondence; Whittlesey, Elisha, -- 1783-1863 -- Correspondence; Parsons family; United States. -- Continental Army -- Officers; Ohio Company (1786-1796); American loyalists; Indians of North America -- Northwest, Old; Land companies -- Ohio; Land speculation -- Ohio -- Marietta; Nullification (States' rights); Connecticut -- History -- 1775-1865; United States -- History -- Revolution, 1775-1783.; Western Reserve (Ohio)